Dampak dan Faktor Penghambat Collaborative Governance dalam Pemberdayaan Petani Jamur di Kelurahan Limau Manis Kecamatan Pauh Kota Padang - Triyanti Nazara, Evi; Eriyanti, Fitri (PUBLICNESS: Journal of Public Administration Studies, 2023)
This study was conducted to discuss the impact and inhibiting factors in Collaborative Governance in empowering mushroom farmers in Limau Manis Village, Pauh District, Padang City. This research was prepared with a qualitative approach and used descriptive methods. And research informants use Purposive Sampling technique. The results of this study are the impact and inhibiting factors of Collaborative Governance in empowering mushroom farmers in Limau Manis Village. The findings in this study show that the impact of the collaboration carried out is the increase in the economy of mushroom farmers, the start of complete equipment in growing mushrooms, the increasing ability of mushroom farmers in growing mushrooms, reducing unemployment in Limau Manis Village, while the inhibiting factors are the lack of synergy with other parties, still lacking commitment, lack of funding, lack of focus of mushroom farmers in mushroom cultivation, limited mushroom production places.